Chronic Hypertension in Pregnancy. Issue 1 (24th March 2021) - Battarbee, A.N.; Sinkey, R.G.; Harper, L.M.; Oparil, S.; Tita, A.T.N.
Abstract : ( Am J Obstet Gynecol . 2020;222:532–541) New guidelines for the management of chronic hypertension have been published in the last 3 years by the American College of Obstetricians and Gynecologists (ACOG), The American College of Cardiology (ACC), The American Heart Association (AHA), and the International Society for the Study of Hypertension in Pregnancy (ISSHP). The authors compiled this work to review the evidence supporting these new guidelines and to provide critiques on areas that need further research.